Association of preoperative inflammatory and nutritional serum markers with post-surgical outcomes in advanced epithelial ovarian cancer patients undergoing primary cytoreductive surgery - Ara, Shamim; Sultana, Jesmin; Tasrin, Liza; Purabi, Ayesha Siddika; Uddin, M. Boyez (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Advanced epithelial ovarian cancer typically presents at later stages, contributing to high morbidity and mortality. Simple, inexpensive biomarkers such as neutrophil-to-lymphocyte ratio (NLR) and serum albumin may help predict postoperative outcomes, particularly in low-resource settings. This study aimed to evaluate the association of preoperative inflammatory and nutritional serum markers with postoperative outcomes among women undergoing primary cytoreductive surgery for advanced epithelial ovarian cancer. Methods: A descriptive observational study was conducted at Dhaka Medical College Hospital from July 2021 to June 2022, including 50 women with advanced epithelial ovarian cancer undergoing primary cytoreductive surgery. Preoperative NLR and serum albumin were measured and categorized (NLR <3.4 vs ≥3.4; albumin ≥3.5 g/dL vs <3.5 g/dL). Postoperative complications within 30 days and the length of hospital stay were recorded. Statistical analyses included Chi-square tests and t-tests, with p<0.05 considered significant. Results: Elevated NLR (≥3.4) was significantly associated with higher rates of wound infection requiring secondary suturing and increased postoperative blood transfusion. Similarly, hypoalbuminemia (<3.5 g/dL) was strongly associated with postoperative wound complications and higher transfusion needs. Both elevated NLR and low albumin were significantly correlated with prolonged hospital stay. Conclusions: Preoperative NLR and serum albumin are valuable predictors of postoperative morbidity and recovery after primary cytoreductive surgery for advanced epithelial ovarian cancer. These readily accessible biomarkers can enhance preoperative risk stratification and guide optimization strategies to improve surgical outcomes.